Pengaruh Burnout dan Work-Life Balance terhadap Turnover Intention dengan Resilience sebagai Variabel Moderasi pada Mitra Pengemudi Ojek Online Generasi Z di Kabupaten Tasikmalaya - Revalina Ekasari; Adi Muhammad Nur Ihsan (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2026)
The gig economy has created unique psychological pressures for workers, particularly Generation Z ride-hailing drivers who navigate algorithm-based work demands with limited institutional protection. Conducted among Generation Z ride-hailing partners in Tasikmalaya Regency, this study investigates how burnout and work-life balance contribute to turnover intention, positioning resilience as a moderating variable within the proposed framework. Purposive sampling was applied within a quantitative research design, yielding 96 participants who satisfied the following inclusion criteria that is between 18 and 29 years of age, holding active partnership status with either Gojek or Grab for a minimum of six months, and residing within Tasikmalaya Regency. A structured Likert-scale questionnaire served as the primary data collection instrument, with Partial Least Squares Structural Equation Modelling (PLS-SEM) via SmartPLS employed for data analysis. Convergent and discriminant validity (AVE > 0.50) alongside satisfactory reliability (Cronbach's Alpha and Composite Reliability > 0.70) were verified across all constructs through measurement model assessment. An R-square value of 0.893 was obtained from the structural model, reflecting strong predictive capability. These findings suggest that among gig workers in a regional setting, perceived work-life imbalance is the dominant driver of turnover intention, while burnout and resilience play less decisive roles. Platform operators should prioritise improving work-life balance schemes as a strategic lever for reducing driver attrition.